Swear Words in French : Analysis of Social Class and Gender - Sajarwa Sajarwa (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2021)
Swear words utterances in French are used as a mean to express emotion that have various functions, both personal or social. The swear words represent social group and gender. This research uses descriptive-interpretative method which data taken from two French novels with different social class background. The research results show that in upper social group, the swear words deliver indirectly, meanwhile in lower social group, the swear words express directly to the party that being cursed. Both social groups use professions as verbal abuse, however the upper social group also uses ethnicity as swear words. Through the swear words, the upper class group preserve their social status from generation to generation. From the gender perspective, men and women both use swear words refer to genitals. Men have more variation of swear words usage.